Emergency Department Management of Chest Pain With a High-Sensitivity Troponin-Enabled 0/1-Hour Rule-Out Algorithm: Impact on Outcomes in a Real-World Setting - Bevins, Nicholas J; Chae, Hyojin; Hubbard, Jacqueline A; Castillo, Edward M; Tolia, Vaishal M; Daniels, Lori B; Fitzgerald, Robert L (American journal of clinical pathology, 2022)
Objectives: The analytical sensitivity of high-sensitivity cardiac troponin T (hsTnT) assays has enabled rapid myocardial infarction rule-out algorithms for emergency department (ED) presentations. Few studies have analyzed the real-world impact of hsTnT algorithms on outcomes and operations. Methods: Comparison of ED length of stay (LOS) and 30-day outcomes (return to ED, inpatient admission, and mortality) for patients presenting with chest pain during 2 separate 208-day periods using a 0/1-hour hsTnT-enabled algorithm or fourth-generation TnT. Results: Discharge, 30-day readmission, and 30-day mortality rates were not significantly different with fourth-generation TnT vs hsTnT. Thirty-day return rates were significantly decreased with hsTnT (17.4% vs 14.9%; P <.01). For encounters with TnT measured at least twice and resulting in discharge, median ED LOS decreased by 61 minutes with the use of hsTnT (488 vs 427 minutes; P <.0001). Median time between first and second TnT results decreased by 82 minutes with hsTnT (202 vs 120 minutes; P <.0001), suggesting that the 0/1-hour algorithm was incompletely adopted. Conclusions: Implementation of the hsTnT algorithm was associated with decreased 30-day return rates and decreased ED LOS for a subset of patients, despite incomplete adoption of the 0/1-hour algorithm. KEY WORDS Troponin; Sensitive; Acute myocardial infarction; Cardiac biomarkers